Cost-effectiveness analysis of a hand hygiene monitoring system in a tertiary pediatric hospital in Mexico - Salinas-Escudero, Guillermo; Rosa-Zamboni, Daniela De la; Carrillo-Vega, María Fernanda; Gamiño-Arroyo, Ana Estela; Toledano-Toledano, Filiberto; Ortega-Riosvelasco, Fernando; Granados-García, Víctor; Villa-Guillén, Mónica; Garduño-Espinosa, Juan (Frontiers in Public Health, 2023)
Background An automated hand-hygiene monitoring system (AHHMS) was implemented in October 2019 at the Hospital Infantil de México Federico Gómez (HIMFG), a tertiary pediatric referral hospital, in four of the hospital wards with the highest rates of Healthcare Associated Infections (HAIs). The clinical and economic impact of this system had not yet been assessed prior to this study. This study aimed to evaluate if the AHHMS is a cost-effective alternative in reducing HAIs in the HIMFG. Methodology A full cost-effectiveness economic assessment was carried out for the hospital. The alternatives assessed were AHHMS implementation vis-a-vis AHHMS non-implementation (historical tendency). The outcomes of interest were infection rate per 1,000 patient-days and cost savings as a result of prevented infections. Infection rate data per 1,000 patient-days (PD) were obtained from the hospital's Department of Epidemiology with respect to the AHHMS. As regards historical tendency, an infection-rate model was designed for the most recent 6-year period. Infection costs were obtained from a review of available literature on the subject, and the cost of the implemented AHHMS was provided by the hospital. The assessment period was 6 months. The incremental cost-effectiveness ratio was estimated. Costs are reported in US Dollars (2021). Univariate sensitivity and threshold analysis for different parameters was conducted. Results The total estimated cost of the AHHMS alternative represented potential savings of 308,927–546,795 US Dollars compared to non-implementation of the system (US464,102 v. US773,029–1,010,898) for the period. AHHMS effectiveness was reflected in a diminished number of infections, 46–79 (−43.4–56.7%) compared to non-implementation (60 v. 106-139 infections). Conclusion The AHHMS was found to be a cost-saving alternative for the HIMFG given its cost-effectiveness and lower cost vis-a-vis the alternate option. Accordingly, the recommendation was made of extending its use to other areas in the hospital.